Pengaruh Masa Kerja dan Tingkat Pengetahuan dengan Ketaatan Penggunaan Alat Pelindung Diri (APD) pada Pekerja di PT.X - Pratama, Muchamad Rafi; Sunaryo, Merry; Rohmah, Mazidatur; Mubarok, Naufal; Sahri, Moch (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Occupational Safety and Health (K3) is very important to note for all workers and company owners. Occupational Safety and Health (K3) is a system created for workers and business owners to prevent work accidents and occupational diseases (PAK). This type of research is an observational descriptive which aims to determine the relationship between tenure and level of knowledge regarding the use of personal protective equipment (PPE). The research design used was cross-sectional. Based on data analysis, the relationship between knowledge and years of service with adherence to the use of personal protective equipment (PPE) in PT. X workers is very influential. many respondents from PT.X workers are reluctant to wear personal protective equipment (PPE) because there are several factors, namely lack of knowledge, lack of years of service and other factors. For PT.X workers who have not used personal protective equipment (PPE) it is expected to be more raise awareness about the importance of using personal protective equipment (PPE) so as to avoid work accidents or occupational diseases (PAK).